(untitled) (Nigerian Journal of Health Sciences, 2023)
Background: Personal music players (PMPs) are widely used among young adults of Nigeria, but information on knowledge about their usage and effect on hearing health has not been studied in Nigeria. Objectives: The aim of the study was to determine the pattern of usage, knowledge and attitude towards loud sound output from PMPs among young Nigerian adults. Methods: This was a prospective, observational survey. Subjects were recruited from a cross‑section of undergraduate students of Obafemi Awolowo University, Ile‑Ife. A structured questionnaire that detailed the type and usage of PMPs was administered. Subjects were also asked about episode of adverse hearing effects and the attitude of the respondents to issue of recreational noise and hearing loss. Results: There were 985 respondents, comprising 594 (60.3%) males and 391 (39.7%) females. Of the 985 students, 967 (98.2%) admitted listening to music on PMPs. The mean age of the student was 24.4 (6.0) years, with 891 (92.1%) of the 967 using earphones while listening to music. Mobile phones were the most common PMPs being used by 768 (79.3%) of the respondents. Five hundred and thirty (54.8%) were listening to music for more 1 h per day and 536 (55.4%) were listening to music for more than 3 days per week. Further, 502 (52.3%) were listening to music at the level of loudness, which was self‑assessed to be high volume. Conclusions: Mobile phones are the most common PMPs in the present study population and most of the respondent were listening to music at the level of loudness that should call for concern.